The Influence of Dividend Policy and Net Profit Margin on Stock Prices in Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Nurhaya Yusuf; A Ratna Sari Dewi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the effect of the dividend policy on stock prices of pharmaceutical sub-sector manufacturing companies on the Indonesia Stock Exchange; to determine the effect of NPM on stock prices of pharmaceutical sub-sector manufacturing companies on the Indonesia Stock Exchange, and to determine the effect of both the dividend policy and NPM together on stock prices of pharmaceutical sub-sector manufacturing companies on the Indonesia Stock Exchange. The population in this study are pharmaceutical companies that carry out dividend policies and net profit margins for the 2016-2020 period by selecting samples using the purposive sampling method so that a sample of five pharmaceutical companies is taken. This research uses the literature study and documentation method. The results showed that the dividend policy (DPR) had a positive and significant effect on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange, while net profit margin (NPM) had no positive and significant effect on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange, and the dividend policy (DPR) and net profit margin (NPM) simultaneously had a significant effect on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange.